Reorientasi Nilai-nilai Kepesantrenan Pada â€œSantri Kalongâ€ Pondok Pesantren Salafiyah Syafiâ€™iyah Sukorejo - Khulusinniyah , Khulusinniyah; Wassalwa, Almannah (Jurnal Pendidikan Islam Indonesia, 2017)
Santri students who live in dormitories are certainly getting an education, teaching and additional guidance outside of school hours, either through interaction among students as well as for the guidance of the matron or from santri more senior. But not so for students Kalongs that do not live in the dorms, they sometimes just be content teaching that was obtained at the time in school, only a few students who got the attention of his parents on education and teaching additional. Quality and knowledge so the inequality between the hostel students and students of bats is very visible. In development, if such a situation is allowed to drag in a prolonged period will bring a very significant impact on the quality and development of the students Kalongs. They will compete with students who are extra hostel always gets hammered and additional knowledge, and without knowing the play time. Unfortunately again, they feared would become a personage students with behavior that is non-students. Conditions such as the need for social governance system study on how to improve students Kalongs are most appropriate to apply Salafiyah Syafi'iyah Sukorejo boarding school in order to reduce the disparities that exist.